Does organizational climate determine interpersonal relationships or do interpersonal relationships determine organizational climate? - Arias Gallegos, Walter (2018)
In this study, the relationship between organizational climate and interpersonal relationships at work were analyzed in order to estimate the impact the first has on the second, and vice versa. To that end, 73 workers from a private business from Arequipa were evaluated using the Likert Organizational Profile and the Workplace Interpersonal Relationships Satisfaction Scale. The results suggest that there are positive and moderate correlations between variables, and that organizational climate has predictive power on interpersonal relationships at work, but not in the opposite way.